Restored retinal physiology after administration of niacin with citicoline in a mouse model of hypertensive glaucoma - Melecchi, Alberto; Amato, Rosario; Dal Monte, Massimo; Rusciano, Dario; Bagnoli, Paola; Cammalleri, Maurizio (Frontiers in Medicine, 2023)
Introduction Much interest has been addressed to antioxidant dietary supplements that are known to lower the risk of developing glaucoma or delay its progression. Among them, niacin and citicoline protect retinal ganglion cells (RGCs) from degeneration by targeting mitochondria, though at different levels. A well-established mouse model of RGC degeneration induced by experimental intraocular pressure (IOP) elevation was used to investigate whether a novel combination of niacin/citicoline has better efficacy over each single component in preserving RGC health in response to IOP increase. Methods Ocular hypertension was induced by an intracameral injection of methylcellulose that clogs the trabecular meshwork. Electroretinography and immunohistochemistry were used to evaluate RGC function and density. Oxidative, inflammatory and apoptotic markers were evaluated by Western blot analysis. Results The present results support an optimal efficacy of niacin with citicoline at their best dosage in preventing RGC loss. In fact, about 50% of RGCs were spared from death leading to improved electroretinographic responses to flash and pattern stimulation. Upregulated levels of oxidative stress and inflammatory markers were also consistently reduced by almost 50% after niacin with citicoline thus providing a significant strength to the validity of their combination. Conclusion Niacin combined with citicoline is highly effective in restoring RGC physiology but its therapeutic potential needs to be further explored. In fact, the translation of the present compound to humans is limited by several factors including the mouse modeling, the higher doses of the supplements that are necessary to demonstrate their efficacy over a short follow up period and the scarce knowledge of their transport to the bloodstream and to the eventual target tissues in the eye.